Strengthening Student Discipline through Security Alliances and Student Discipline - Syaifuddin, Muhammad Arif; Saputra, Bachtiar Adi (EDUMALSYS Journal of Research in Education Management, 2023)
Student discipline needs to be strengthened to face the challenges of the digital era faced by the millennial generation, especially in facing an era that continues to grow rapidly. This research is expected to produce findings in the form of an illustration of strengthening the discipline of junior high school students in facing the challenges of the digital era through the existence of a disciplinary team named Al Asad (Student Security and Discipline Alliance). This research is an analytical descriptive study so that as much data as possible is obtained using various techniques arranged systematically. The objects in this qualitative study consisted of students in grades 7 to 9, Al Asad administrators, teachers and school principals at SMP Muhammadiyah 2 Taman. AL-ASAD is an innovation from the school by involving the active role of peers in strengthening and increasing the discipline of students at SMP Muhammadiyah 2 Taman. Examples of good discipline that should be applied are praying five times a day, not being late for school, attending all ongoing lessons, taking care of school facilities as well as possible, and so on. The conclusion of this study is that AL-ASAD is an effort to strengthen and improve the discipline of students at SMP Muhammadiyah 2 Taman through several positive activities including prayer patrols, guarding the entrance gate and playing an active role in enforcing rules related to Islamic law. Based on input from various parties, there are several improvements that need to be made, including the sorting of punishment in the form of Istighfar, which needs to be reviewed.